Analysis and Evaluation of Agricultural Non-point Source Pollution Sources in Four Cities in the Pearl River Delta - XIA Lijia; YU Muqin; YAN Meng; JIANG Yu; XIONG Jing (Renmin Zhujiang)
Based on the 2018 statistical yearbook,this paper carries out the statistics and analysis on the agricultural non-point source pollution of the four major economic cities,namely Guangzhou,Dongguan,Shenzhen and Foshan in the Pearl River Delta by the inventory analysis method.The study found that:In 2018,the four cities in the Pearl River Delta produced 137 179.3 tons of COD,19 345.5 tons of TN,2 865.2 tons of TP,and 2 926.4 tons of NH+4-N from agricultural non-point source pollution,among which the COD is considered as the primary pollutant,mainly from livestock and poultry breeding,while TN,NH+4-N and TP mainly come from rural life and planting industry.In terms of regions,the pollutant emission intensity of Foshan is 427.42 kg/hm2,which is 1.5 times that of Guangzhou,ranking first among the four cities.The comprehensive water quality index caused by agricultural non-point source pollution in Guangzhou and Foshan is both greater than 4,so the two cities are considered as severely polluted areas,with heavy pressure to reduce agricultural non-point source pollution,while Dongguan and Shenzhen are lightly polluted areas.